1999
DOI: 10.1046/j.1365-2249.1999.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive characterization of the immunophenotype and pattern of cytokine production by distinct subpopulations of normal human peripheral blood MHC II+/lineage−  cells

Abstract: SUMMARYDendritic cells (DC) represent the most powerful professional antigen-presenting cells (APC) in the immune system. The aim of the present study was to analyse, on a single-cell basis by multiparametric ow cytometry with simultaneous four-colour staining and a two-step acquisition procedure, the immunophenotypic pro®le and cytokine production of DC from 67 normal whole peripheral blood (PB) samples. Two clearly different subsets of HLA-II /lineage À were identi®ed on the basis of their distinct phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…Owing to the important role of regulatory cytokines of DC origin in the induction and activation of immune responses, we evaluated the cytofluorimetric DC expression of IL-12 and IL-10, both in basal and stimulated conditions. We used LPS as the DC stimulator because LPS, with or without IFN-g, has been reported to be the optimal stimulus for analysis of cytokine expression by DCs in whole-blood samples (Almeida et al, 1999;Bueno et al, 2001), and because TLR4, which is required for the response to LPS, is selectively expressed on myeloid CD11c þ DCs (Krug et al, 2001). We found that DC constitutive production of IL-10 was increased in patients with invasive cancer, while that of IL-12 was similar to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the important role of regulatory cytokines of DC origin in the induction and activation of immune responses, we evaluated the cytofluorimetric DC expression of IL-12 and IL-10, both in basal and stimulated conditions. We used LPS as the DC stimulator because LPS, with or without IFN-g, has been reported to be the optimal stimulus for analysis of cytokine expression by DCs in whole-blood samples (Almeida et al, 1999;Bueno et al, 2001), and because TLR4, which is required for the response to LPS, is selectively expressed on myeloid CD11c þ DCs (Krug et al, 2001). We found that DC constitutive production of IL-10 was increased in patients with invasive cancer, while that of IL-12 was similar to controls.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the incubation period, samples were aliquoted and labelled with appropriate combinations of mAbs for staining of surface markers. Cells were then fixed, permeabilised and stained with cytokine-directed mAbs anti-IL-12 PE and anti-IL-10 PE (Caltag Laboratoires), using the Fix & Perm reagent (Caltag Laboratoires) (Almeida et al, 1999;Bueno et al, 2001). Cytokine-directed mAbs were used at saturating concentrations and conditions.…”
Section: Cytoplasmic Cytokine Expressionmentioning
confidence: 99%
“…19 Importantly, we and many others have reported the existence of acute leukemias and plasmacytoid dendritic cell (pDC) leukemias (450%) lacking MLL rearrangements but expressing NG2 (Table 1). [60][61][62] Based on the controversial data about the clinical relevance of NG2 expression together with the existence of NG2-expressing acute leukemias lacking MLL rearrangements, in particular pDC leukemias, 60,61 we wanted to gain further insight into the biological association between NG2 expression and MLL rearrangements. We analyzed whether the expression of NG2 may depend on the particular gene(s) paired to MLL when it is rearranged and we also explored the hypothesis that the expression of NG2 in leukemias lacking MLL rearrangements, such as NG2 þ pDC leukemias, may be due to the existence of a minor subset of CD34 þ hematopoietic stem/progenitor cells readily coexpressing NG2 wherein the leukomogenesis process may be initially triggered.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…In this step, a minimum of 3 ϫ 10 5 events from the total PB cellularity was measured in order to obtain information on at least 1000 dendritic cells defined as being MHC II ϩ /lineage Ϫ cells (non-T, non-B, non-NK and non-monocytic cells) for further immunophenotypic analysis. 26 For data analysis, the Paint-A-Gate PRO software was used. Identification and enumeration of the relative numbers of the different CD34 Ϫ cell subsets present in PB was performed as shown in Figure 1.…”
Section: Immunophenotypic Analysis Of Pb Recovery Of Cd34 ϫ Hemopoietmentioning
confidence: 99%